Context Processing and the Neurobiology of Post-Traumatic Stress Disorder - Liberzon, Israel (Neuron, 2016)
Progress in clinical and affective neuroscience is redefining psychiatric illness as symptomatic expression of cellular/molecular dysfunctions in specific brain circuits. Post-traumatic stress disorder (PTSD) has been an exemplar of this progress, with improved understanding of neurobiological systems subserving fear learning, salience detection, and emotion regulation explaining much of its phenomenology and neurobiology. However, many features remain unexplained and a parsimonious model that more fully accounts for symptoms and the core neurobiology remains elusive. Contextual processing is a key modulatory function of hippocampal-prefrontal-thalamic circuitry, allowing organisms to disambiguate cues and derive situation-specific meaning from the world. We propose that dysregulation within this context-processing circuit is at the core of PTSD pathophysiology, accounting for much of its phenomenology and most of its biological findings. Understanding core mechanisms like this, and their underlying neural circuits, will sharpen diagnostic precision and understanding of risk factors, enhancing our ability to develop preventive and “personalized” interventions.